A comparative study between the synthetic and synthesized hydroxyapatite derived from the natural shell waste and coating on AZ31 alloy: Enhanced mechanostructural and corrosion properties - Aver, M.; Pihtili, H.; Aksakal, B. (Elsevier Sci Ltd, 2025)
AZ31 has good potential in biomedical arena due to its similar Young's modulus to bone and the low toxicity of Mg ion, however, especially possessing low biological corrosion resistance limits its potential usage. The surfaces of the AZ31 implant material were coated with commercially available synthetic-sHAp and chemically synthesized Hydroxyapatite (nHAp) obtained from natural waste sources (nHAp) to increase the corrosion resistance of the alloy. The nHAp was obtained from waste shell sources (chicken eggshell- CS, Ostrich eggshell-OS, and Mussel shell-MS) syntesized by sol gel-calcination and chemical synthesis method. These synthesized nHAps and commercial synthetic sHAp were coated on AZ31 surfaces in four different groups (CS-nHAp, OSnHAp, MS-nHAp, and sHAp) by the electrophoretic deposition method (EPD) and were sintered in an argon atmosphere at 450 degrees C. The surface morphologies of the obtained coatings were characterized by scanning electron microscopy (SEM), X-ray diffractometer (XRD), and Fourier-transform infrared spectroscopy (FT-IR). The hardness and adhesion strength of the coated surfaces of AZ31 were measured. The effect of coating parameters on the corrosion resistance has been analysed and determined by in vitro potentiodynamic polarization (PDS) and three electrode techniques. Higher adhesion strength values were obtained in OS-nHAp group samples than were found in sHAp group samples. From the wettability analysis, it was observed that the OS-nHAp group showed superhydrophilic characteristics. On the basis of current comparative analysis, the corrosion resistance of the AZ31 samples coated with OS-nHAp was found to be the highest compared to other sHAp and nHAp groups, and they are offered as a possible biological material for relevant applications.
Keywords: Bio-wastes; Shell derived hydroxyapatite; Mg alloy-AZ31; Electrophoretic deposition; Corrosion